Neutral Processes Drive Seasonal Assembly of the Skin Mycobiome - Xinzhao Tong; Marcus H. Y. Leung; David Wilkins; Hedwig H. L. Cheung; Patrick K. H. Lee (mSystems, 2019)
ABSTRACT The importance of microorganisms to human skin health has led to a growing interest in the temporal stability of skin microbiota. Here we investigated the dynamics and assembly of skin fungal communities (mycobiomes) with amplicon sequencing of samples collected from multiple sites on 24 healthy Chinese individuals across four seasons (in the order of winter, spring, summer, and autumn in a calendar year). We found a significant difference in community compositions between individuals, and intrapersonal community variation increased over time at all body sites. Within each season, the frequency of occurrence of most operational taxonomic units (OTUs) was well fitted by a neutral model, highlighting the importance of stochastic forces such as passive dispersal and ecological drift in skin community assembly. Despite the significant richness contributed by neutrally distributed OTUs, skin coassociation networks were dominated by taxa well-adapted to multiple body sites (forehead, forearm, and palm), although hub species were disproportionately rare. Taken together, these results suggest that while skin mycobiome assembly is a predominantly neutral process, taxa that could be under the influence of selective forces (e.g., host selection) are potentially key to the structure of a community network. IMPORTANCE Fungi are well recognized members of the human skin microbiota and are crucial to cutaneous health. Common cutaneous diseases such as seborrheic dermatitis and dermatophytes are linked to fungal species. Most studies related to skin microbial community dynamics have focused on Western subjects, while non-Western individuals are understudied. In this study, we explore the seasonal changes of the skin mycobiome in a healthy Chinese cohort and identify ecological processes that could possibly give rise to such variations. Our work reveals the dynamic nature of host skin fungal community, highlighting the dominant roles neutral forces play in the seasonal assembly of skin mycobiome. This study provides insight into the microbial ecology of the human skin microbiome and fills a knowledge gap in the literature regarding the dynamics of skin fungal community.